HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SIDOSERMO SURABAYA - Anugrah Linda Mutiarani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
Objective to know the family support with Exclusive Breastfeeding in the working area of Sidosermo Public Health Service Surabaya. Materials and methods this study is analytic observational. Using cross sectional approach. Consist of 21 samples taken using purposive sampling method at Margorejo and Sidosermo Sub-district. The independent variable is family support, while the dependent variable is exclusive breastfeeding. To know the relationship of family support and Exclusive breast feeding, Chi Square statistic test, with significance limit, p value <0,05. Results there was a significant relationship (p = 0.027) between family support and exclusive breastfeeding. Conclusion there is a relationship between family support and Exclusive Breastfeeding in Margorejo and Sidosermo Sub-district.